Effects of superparamagnetic iron oxide nanoparticles and static magnetic fields on neural stem cell differentiation by transcriptomic techniques - Dan Li; Xiangyu Ma; Mingliang Tang (STEMedicine, 2022)
Neural stem cells (NSCs)-based cell therapy provides promising treatment for the neurodegenerative diseases. The success of stem cell therapy relies on the efficient differentiation of transplanted stem cells into functional cells. Therefore, directed differentiation of NSCs into neurons is essential for its application in the neurodegenerative diseases. In recent years, magnetic fields and superparamagnetic iron oxide nanoparticles (SPIOs) have shown potential in the regulation of stem cell behaviors. Here, we investigated the regulatory effects of static magnetic fields (SMFs) and the combination with SPIO on NSC differentiation by transcriptome sequencing analysis techniques. Our results found that SPIOs caused more differentially expressed genes than SMF alone. Interestingly, the number of differentially expressed genes induced by the combination was less than that of SPIO alone, which may imply that the regulation is not a simple superposition effect. Our findings provide experimental evidence for the regulation of SMF and SPIO on NSC differentiation at the transcriptomic level.